A Long and Consistent Life of Creating: James Krenov, Cabinetmaker and Teacher. Issue 1 (2nd January 2017) - Barty, Taimi
Abstract : James Krenov (1920–2009), a lifelong cabinetmaker and teacher, demonstrated and encouraged a balance of discipline and playfulness in his work and writings. He gave voice to woodworkers who objected to the commercialism of creativity. Taimi Barty, a student of Krenov, explores his physical workspaces throughout his life in an effort to understand his effectiveness in inspiring an international audience of craftspeople.